2019
DOI: 10.1002/rrq.259
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Influence of Peer Feedback and Author Response on Chinese University Students’ English Writing Performance?

Abstract: Enhancing writing pedagogy in university‐based courses for students of English as a foreign language has been a long‐term goal of educators and researchers. Most recent work, however, has relied on qualitative methodologies that limit our capacity to generalize findings. In this quantitative study, the authors adopted a quasi‐experimental control group design to investigate effects of peer feedback and author response on university students’ writing performance in a context of English as a foreign language. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 76 publications
1
23
0
1
Order By: Relevance
“…Yet, there is still no conclusive evidence concerning the efficacy of specific feedback strategies in improving second language (L2) learners' writing accuracy. L2 researchers, to date, have investigated the effect of feedback on L2 learners' writing ability from different perspectives, including focused and unfocused feedback (e.g., Bitchener & Knoch, 2009;Nemati, Alavi, & Mohebbi, 2019), direct and indirect feedback (Karim & Endley, 2019;Kim & Bowles, 2019), the feedback medium (Zhang, 2020), L2 learners and teachers' perceptions, preferences, needs, and practices in writing tasks (Bahrouni & Tuzlukova, 2019;Motallebzadeh, Kondori, & Kazemi, 2020;Nemati, Alavi, Mohebbi, & Masjedlou, 2017;Raza, 2019), and the source of feedback, namely teacher and/or peer (Ferris, 1995;Hyland, 2000;Miao, Badger, & Zhen, 2006;Peterson & Portier, 2014;Zhang & McEneaney, 2020). These studies and their inconclusive and somehow contradictory findings have given rise to a great deal of discussion on the value of feedback in developing writing accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there is still no conclusive evidence concerning the efficacy of specific feedback strategies in improving second language (L2) learners' writing accuracy. L2 researchers, to date, have investigated the effect of feedback on L2 learners' writing ability from different perspectives, including focused and unfocused feedback (e.g., Bitchener & Knoch, 2009;Nemati, Alavi, & Mohebbi, 2019), direct and indirect feedback (Karim & Endley, 2019;Kim & Bowles, 2019), the feedback medium (Zhang, 2020), L2 learners and teachers' perceptions, preferences, needs, and practices in writing tasks (Bahrouni & Tuzlukova, 2019;Motallebzadeh, Kondori, & Kazemi, 2020;Nemati, Alavi, Mohebbi, & Masjedlou, 2017;Raza, 2019), and the source of feedback, namely teacher and/or peer (Ferris, 1995;Hyland, 2000;Miao, Badger, & Zhen, 2006;Peterson & Portier, 2014;Zhang & McEneaney, 2020). These studies and their inconclusive and somehow contradictory findings have given rise to a great deal of discussion on the value of feedback in developing writing accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The study's findings revealed that the students in the experimental group outperformed the students in the control group. Similarly, Zhang and McEneaney (2020) conducted a 15-week research study to analyse the differences between teacher feedback and peer feedback in writing among 198 major English students. The outcomes of the analyses showed that the peer feedback group demonstrated a significantly better writing performance improvement than the traditional teacher feedback group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Being accustomed to tackling writing as a solitary task, students might find it somehow challenging to adopt a more "collaborative mindset" (Blau and Caspi, 2009, p.49). For example, they might be reluctant to change or revise other students" written products (Zhang, 2018). From another perspective, writers themselves might not be tolerant towards their peers" revision (Chen, 2014).…”
Section: Collaborative Writingmentioning
confidence: 99%
“…It was concluded also that online peer feedback is more influential than offline feedback, because it is easier for the teacher to refer to peers" comments and evaluate their impact on students" writing. Yet, Zhang (2018) proved that the quality of EFL students" feedback is not the only factor that matters in online peer revision. He proposed that the quality of writers" response to revision, or what is called (backfeedback), had a slightly larger impact than students" feedback.…”
Section: Online Peer Feedbackmentioning
confidence: 99%